Music, life, and changing times : selected correspondence between British composers Elizabeth Maconchy and Grace Williams, 1927-77 /: selected correspondence between British composers Elizabeth Maconchy and Grace Williams, 1927-77. (2020) - Maconchy, Elizabeth, 1907-1994; Williams, Grace, 1906-1977
No abstract available